An experimental investigation on performance of microencapsulated phase change material slurry in ground heat exchanger. (October 2022) - Xu, Lingling; Pu, Liang; Angelo, Zarrella; Zhang, Derun; Dai, Minghao; Zhang, Shengqi
Abstract: As a promising alternative to conventional heat transfer fluids, microencapsulated phase change material slurry (MPCS) was applied in ground heat exchanger (GHE) in this paper. A sandbox system embedded with horizontal serpentine GHE was installed and MPCS using N-eicosane (C20 H42 ) as phase change material is prepared. To explore the merits of MPCS, a comparison study between performance of water and MPCS was conducted. In addition, the enhanced heat transfer mechanism of MPCS were studied by comparing performance of MPCS with different inlet temperature and particle concentration. The experimental results indicate that the heat transfer rate and pumping consumption of 25 wt% MPCS with inlet temperature of 30 °C are 10.5 and 2.8 times that of water, respectively. The heat load-to-pumping consumption ratio has an enhancement of 3.73 times in comparison to water. Obviously, considering the phase transition process, MPCS can efficiently improve thermal performance of GHE. However, in the non-phase transition temperature range, the performance of MPCS is even worse than that of water. The comprehensive performance factor of 15 wt% MPCS and 25 wt% MPCS with inlet temperature of 38 °C declined by 45.6% and 36.9% in comparison with pure water.